Mysteries underground - Friedberg, Lionel (The Society, 1992)
Journey with the underworld of caves, including the deepest and exotic cave, the new Mexico a Lechuguilla. Other twisting, dripping, gleaming underground wonders also includes the Mammoth and Flint Ridge Cave system creating the longest cave network in the world.